THE MEDIATING ROLE OF BRAND TRUST IN THE EFFECT OF CUSTOMER REVIEWS, INFLUENCER, AND PRICE ON PURCHASE DECISIONS OF SOMETHINC BEAUTY PRODUCTS ON SHOPEE - Rafda Hasna Imamah; Prasetyo Hartanto; Lina Fatimah Lishobrina (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The rapid growth of e-commerce in Indonesia has transformed consumer behaviour in the beauty industry, particularly through Shopee as a dominant marketplace and Somethinc as a leading local beauty brand. This study aims to examine the mediating role of brand trust in the relationship between customer reviews, influencers, price, and purchase decisions of Somethinc beauty products on Shopee. A quantitative approach was employed through an online survey involving 270 Indonesian consumers who had purchased Somethinc products on Shopee, selected using purposive sampling. The research constructs were measured using a seven-point Semantic Differential scale, and the data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4.1. The findings reveal that customer reviews, influencers, and price have positive and significant effects on both brand trust and purchase decisions. Brand trust also significantly mediates the relationship between these three variables and purchase decisions, indicating partial mediation. The model explains 53.7% of the variance in purchase decisions and 30.2% in brand trust, with customer reviews identified as the strongest predictor. These findings highlight the importance of brand trust in strengthening digital marketing strategies for local beauty brands in e-commerce platforms.